Strategy to Enhance Competitive Advantage Through Culture Analysis and Customer Behaviors on the Iron Clan Jewelry Brand - Yudha Aditya Gozali Tahir; Putu Nina Madiawati; Mahir Pradana (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This research aims to analyze strategies to increase competitive advantage through cultural analysis and customer behavior in the Iron Clan Jewelry brand. The jewelry industry in Indonesia showed significant growth, with an export value of USD 547.5 million in December 2023. However, jewelry companies face challenges in understanding increasingly complex and dynamic consumer preferences. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to analyze the relationship between variables. Data were collected through a survey of 384 respondents who are consumers or potential consumers of Iron Clan Jewelry in the Greater Bandung area. The research results indicate that cultural analysis and customer behavior significantly influence competitive advantage, with product innovation serving as a key mediator in this relationship. Furthermore, regulation moderates these dynamics, shaping the extent to which cultural insights and consumer feedback can be effectively translated into market advantages. The findings suggest that a deep understanding of cultural values and consumer behavior patterns enables companies to design more relevant and differentiated products, thereby strengthening their competitive position. This study provides strategic recommendations for jewelry brands to leverage cultural insights and adaptive innovation processes while aligning with regulatory frameworks to achieve sustainable growth in a competitive market.